2019
DOI: 10.2478/quageo-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

The concept of social risk: A geographical approach

Abstract: Social risk is an interdisciplinary concept used with various meanings in the social and in the natural sciences. The article presents some of the social insights into this concept, particularly in connection with the global environmental research project and with geography. The special dimension of social risks, as well as some current methodological aspects regarding models and the main indicators used in the multidimensional assessment of social risks are analysed at local, regional and national levels. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Muñoz‐Torres et al (2018), based on the criteria that are used by ESG rating agencies to evaluate corporate sustainability performance, indicated that diversity, human rights, nondiscrimination and promotion of equality are the most relevant in the social domain. Lock and Seele (2015) focused on fair treatment of employees, human rights, and ethical issues in this field, while Lupu (2019) stated that the main sources of social risks are labor‐market instability, social relations of communities, and political transformations. Rehman et al (2020) divided social obligations into four broad categories that a socially responsible organization would like to perform: legal, economic, philanthropic, and ethical responsibilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Muñoz‐Torres et al (2018), based on the criteria that are used by ESG rating agencies to evaluate corporate sustainability performance, indicated that diversity, human rights, nondiscrimination and promotion of equality are the most relevant in the social domain. Lock and Seele (2015) focused on fair treatment of employees, human rights, and ethical issues in this field, while Lupu (2019) stated that the main sources of social risks are labor‐market instability, social relations of communities, and political transformations. Rehman et al (2020) divided social obligations into four broad categories that a socially responsible organization would like to perform: legal, economic, philanthropic, and ethical responsibilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At stage one, statistical data on the progress of the pandemic of the Baltics were selected based on the reliability of the source, representativeness, and the relevance of described parameters. All these requirements were met by data from the World Health Organisation, 2 the European Centre for Disease Prevention and Control (CDC), 3 and reports from the ministries of health of Latvia, 4 Lithuania, 5 and Estonia. 6 These sources provided comprehensive coverage of threats and risks of the pandemic as well as of the national strategies for mitigating them.…”
Section: The Stages and Central Concepts Of The Studymentioning
confidence: 99%
“…4 Veselibas ministrija. URL: https://www.vm.gov.lv/lv/ (accessed 01.09.2020) 5 Ministry of Health of the Republic of Lithuania. URL: https://sam.lrv.lt/en/ (accessed 01.11.2020).…”
Section: The Stages and Central Concepts Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The foreign researchers also pay an attention to the problem's inter-discipline character of the appearance of the ecologically-dependent diseases and the environmental risk, among their number they separate such risk's factors: the behavioral, physiological, demographic, ecological, genetic ones [22], speak on the necessity to unite the efforts of geography, psychology, sociology, law, economics, the public policy in the researches of the social risks [33]. Thus, in our opinion, the very such multi-factuality and the inter-discipline should become the leading characteristic feature, positing the problem of the geographic research of the population's ecologically-caused diseases.…”
Section: Literature Reviewmentioning
confidence: 99%